Growth promotion of sweet basil by arbuscular mycorrhizal fungi and a marine bacterium - Chiquito-Contreras, Roberto Gregorio; Solis-Palacios, Rocio; Reyes-Pérez, Juan José; Reyes, Juan; Murillo-Amador, Bernardo; Alejandre-Rosas, Jorge; Hernández-Montiel, Luis Guillermo (Acta Universitaria, 2019)
The beneficial soil microorganisms is an alternative to increase the growth and productivity of crops such as sweet basil (Ocimum basilicum L.). The objective of this study was to determine the effect of arbuscular mycorrhizal fungi (AMF) and Stenotrophomonas rhizophila on the growth of sweet basil var. Nufar plants. In addition, the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity and biological nitrogen fixation (BNF) were determined in the bacterium. Sweet basil plants were inoculated with two AMF consortia (ORECIB01 and SALCIB01) and marine bacteria. Height, stem length and root length, leaf area, biomass, chlorophyll, mycorrhizal colonization and bacterial population were quantified. The results show that the simultaneous inoculation of ORECIB01 and bacteria significantly promoted all the morphological parameters and chlorophyll in the plants. The AMF-bacteria interaction increased mycorrhization and bacterial population. The biological fertilization of sweet basil plants can be a viable option in the organic and sustainable management of the crop.